1998
DOI: 10.1023/a:1022184704174
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Victimization of Lesbian, Gay, and Bisexual Young People: A Structural Model Comparing Rural University and Urban Samples

Abstract: Research indicates that antigay victimization is widespread and that lesbian, gay, and bisexual young people may be very vulnerable to such victimization. The current study builds upon previous work by Hershberger and D'Augelli (1995), who studied the consequences of sexual orientation-based victimization in 194 urban lesbian, gay, and bisexual youths. Using structural equation modeling, the present study models both antecedents and consequences (including psychological distress, self-esteem, and suicidality) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 34 publications
5
115
2
1
Order By: Relevance
“…This suggests a causal role for self-esteem, presumably indicating that some bisexual men may be resisting homosexuality because of social stigma and other factors, and that the greater self-acceptance of people high in self-esteem makes them more willing to accept their homosexuality. When homosexuals are attacked or victimized for being gay, however, their self-esteem drops afterward (Waldo, Hesson-McInnis, & D'Augelli, 1998). Thus, being victimized leads to lower self-esteem, which is consistent with the findings on bullying we reported earlier.…”
Section: Sexual Behaviorsupporting
confidence: 91%
“…This suggests a causal role for self-esteem, presumably indicating that some bisexual men may be resisting homosexuality because of social stigma and other factors, and that the greater self-acceptance of people high in self-esteem makes them more willing to accept their homosexuality. When homosexuals are attacked or victimized for being gay, however, their self-esteem drops afterward (Waldo, Hesson-McInnis, & D'Augelli, 1998). Thus, being victimized leads to lower self-esteem, which is consistent with the findings on bullying we reported earlier.…”
Section: Sexual Behaviorsupporting
confidence: 91%
“…A composite variable was created by calculating the mean of all items. Previous research using this composite variable has demonstrated adequate internal consistency in a sample of LGB youth (α = .76; Waldo et al, 1998), and our previous work has demonstrated the utility of using this measure as a composite variable (Liu and Mustanski, 2012). The Cronbach's α in our sample ranged from .77 to .93 across all fi ve waves.…”
Section: Methodsmentioning
confidence: 58%
“…6,7,12,[17][18][19][20][21] Few studies of prevention interventions targeting GLB adolescents have been published. Environmental factors associated with sexual orientation play a major role in predicting psychological distress among GLB youths.…”
mentioning
confidence: 99%